(untitled) (Discourse of Law and Administration, 2019)
From the constitutional provision itself, we have two key norms for a citizen wanting to participate in the life of their local government are: participation in sessions of municipal councils, poviat councils or regional councils and the possibility of recording these sessions. The polish Act on Access to Public Information imposes on the authorities the obligation to ensure audibility and accessibility in the rooms where meetings are held as well as the possibility of obtaining documents regarding the work of the council and the local law. Local government laws increase the citizen’s rights at these meetings by: the opportunity to participate in the debate about the state of concrete local government or indirectly by a civic legislative initiative. The postulated institution of a “public hearing”, which could be regulated in the statutes and, for example, local law related with a civic legislative initiative, could increase the interest of citizens in using the right of admission to meetings of collective bodies of local government. There is a lack of precise regulations on the basis acts (and only many acts of local government) issues related to the possibility of citizens taking the floor or go out them, in certain circumstances, from the meeting room.